Making Activation for Young Welfare Recipients Mandatory - Espen S. Dahl; Øystein Hernaes (Institute of Labor Economics (IZA), 2022)
Activation policies to promote self-sufficiency among recipients of welfare and other types of benefits are becoming more common in many welfare states. We evaluate a law change in Norway making welfare receipt conditional on participation in an activation program for all welfare recipients below the age of 30. Analyzing the program's staggered implementation across municipalities with several modern event study estimators, we estimate that the law change had quite precise 0-effects on benefit receipt, work and education. We also do not find any effects on the probability of being out of work or of being in employment, education or labor market programs. Qualitative evidence suggests that the zero effect may be due to the law change only impacting the participation of recipients with low expected gain from activation.
Keywords: H55; I38; J18; 330; social assistance; activation; conditionality; welfare reform; labor